Clinical significance of the overgrown follicles in dromedary camels: prevalence, risks, hemodynamics and response to prostaglandin F2α - Ali, Ahmed; Derar, Derar R.; Alharbi, Yousef M. (Frontiers in Veterinary Science, 2025)
AimThis study investigated the prevalence, associated risk factors, hemodynamic characteristics, and response to prostaglandin F₂α (PG) of overgrown follicles (OVGF) in dromedary camels.Materials and methodsIn Experiment 1, 338 females were examined for breeding soundness during the breeding season to determine the prevalence and risk factors of OVGFs (>2 cm in diameter). In Experiment 2, 45 females were categorized by follicular structure and scanned with spectral Doppler ultrasonography. In Experiment 3, 14 barren females with OVGFs were given PG treatment and monitored for hormonal changes and fertility outcomes.ResultsOVGFs were found in 16.6% of the camels examined, with single (55.5%), double (35.7%), and triple (8.9%) follicles. The majority of affected ovaries contained growing or mature follicles (60.6%) or corpora lutea (3.7%), while 35.7% lacked any additional structures. OVGFs were linked to ovarian hydrobursitis (OVHB, 50%), clinical endometritis (CE, 35.7%), normal genitalia (12.5%), and pregnancy (1.8%). Significant risk factors were OVHB (OR = 27.5; p = 0.002) and CE (OR = 24.7; p = 0.004). Larger and trabeculated OVGFs showed increased systolic and diastolic velocities, a lower resistive index, and a different pulsatility index, indicating improved vascularization with follicular advancement. Complete regression followed by conception occurred in 2/14 animals, partial regression in 8/14 (with one conception), and no regression in 4/14, indicating a limited response to PG therapy. PG administration increased estradiol-17β levels but did not significantly impact progesterone or prolactin levels.ConclusionIn conclusion, overgrown follicles are relatively frequent in dromedary camels and are frequently associated with genital pathologies, particularly ovarian hydrobursitis and endometritis. Their variable vascularization and limited response to prostaglandin treatment suggest that OVGFs may be a persistent follicular condition with low therapeutic reversibility, which has implications for camel fertility management.